The Effect Of Problem Based Learning Model Based On Geographic Literature On Spatial Intelligence Of High School Students - Novia Fitria Istiawati; Sudarmi Sudarmi; Nani Suwarni (Journal Learning Geography, 2021)
The purpose of this study was to determine the effect of the Problem Based Learning model based on geographic literacy on spatial intelligence. This study includes a quasi-experimental design with a nonequivalent pretest-posttest control group design. The research subjects are students of SMAN 1 Way Jepara, X Social which will be selected for the experimental class, control class, and instrument test class. The research instrument consisted of spatial intelligence test questions in the form of a description/essay consisting of 8 questions. Data collection techniques were carried out through observation, tests, and documentation. Analysis of research data was carried out through descriptive statistical methods and parametric inferential statistics with hypothesis testing using the Independent Samples T-test (assisted by SPSS 23 for Windows). The results of this study is the Problem Based Learning model based on geographic literacy has an effect on spatial intelligence in the hydrosphere material of high school students.